Sustainable Ways and Methods of Recycling Epoxy Fiberglass Waste. Issue 3 (November 2021) - Yakovlev, Grigory; Khozin, Vadim; Abdrakhmanova, Lyaila; Maisuradze, Natalia; Medvedev, Vladislav; Grechkin, Pavel; Polyanskikh, Irina; Gordina, Anastasiya; Elrefai, Ali Elsaed Mohamed Mohamed; Zakirov, M. F.
Abstract: This article presents two technological ways of recycling the wastes of the production and application of products made of highly oriented fiberglass bound by the epoxy matrix. The first technology is aimed at shredding the epoxy-based products obtained by pultrusion to create fine and ultrafine powders (up to 2-10 microns) used as fillers in various composites. The second technology offers a way to obtain coarse powders with a particle size of up to 100 microns, used in the composition of heat-insulating materials and fire-retardant intumescent coatings. Proposed is the mechanical grinding of fiberglass to a finely dispersed state with subsequent heating to a temperature of 400 °C in the presence of a foaming coke and liquid glass. This technology allows the full utilization of waste from the production and application of epoxy fiberglass, such as windmill blades and parts of molded products, leading to the creation of an environmentally friendly fire-resistant and heat-insulating material in the form of plates, blocks and other products with operation temperature up to 400C, as well as fire retardant coatings for building materials and structures. By varying the content of the foaming agent and soluble glass in the composition of the intumescent mixture, one can regulate the average density, thermal conductivity and strength of the material within significant limits, achieving characteristics that exceed those of traditional heat-insulating materials. The proposed material based on recycled epoxy fiberglass is inflammable and resistant to unfavorable environmental impacts; it has high biostability and provides heat and mass transfer during the operation in buildings and structures.